Displacement measurement of a concrete bridge under traffic loads with fibre-reinforced polymer-packaged optical fibre sensors. (March 2020) - Tang, Yongsheng; Cang, Jigang; Yao, Yandong; Chen, Ce
Current displacement measurement methods cannot cope with the demands of the long-term measurement of small- or medium-span concrete bridges because of some technology or economic challenges. In this article, a displacement measurement method is proposed for concrete bridges based on fibre-reinforced polymer-packaged optical fibre sensors. The sensing principle and manufacture process of the proposed sensor are introduced as well as the strain sensing property. Then, a relationship is established between the strain and the displacement based on the distributed strain monitoring. Finally, some field tests are implemented using a simply supported concrete bridge. The tests include static loading test, dynamic loading test with specific speeds and dynamic random traffic loading test. The field test results show that the proposed method can measure the displacement of concrete bridges under traffic loads with reasonable accuracy. Moreover, different types of sensor distributions are proposed to investigate the displacement measurement effects to optimise the sensor installation. Although the sensors cover only some key parts of the girder, the results also verify the accuracy of the proposed method. Therefore, the proposed method can be implemented in concrete bridges in future.